Specific plasma metabolite profile in intestinal Behçet’s syndrome - Cheng-cheng Hou; Hua-fang Bao; Chun-hui She; Hua-yu Chen; Guan-xing Pan; Hua-ning Chen; Hong-bing Rui (Orphanet Journal of Rare Diseases)
Abstract Background Intestinal Behçet’s syndrome (IBS) has high morbidity and mortality rates with serious complications. However, there are few specific biomarkers for IBS. The purposes of this study were to investigate the distinctive metabolic changes in plasma samples between IBS patients and healthy people, active IBS and inactive IBS patients, and to identify candidate metabolic biomarkers which would be useful for diagnosing and predicting IBS. Methods In this study, we performed a global untargeted metabolomics approach in plasma samples from 30 IBS patients and 20 healthy subjects. P value < 0.05 and variable importance projection (VIP) values > 1 were considered to be statistically significant metabolites. Univariate receiver operating characteristic (ROC) curve analysis was plotted as a measure for assessing the clinical performance of metabolites, and area under curve (AUC) were assessed. Results A total of 147 differentially abundant metabolites (DAMs) were identified between IBS patients and normal control (NC) group. The potential pathways involved in the pathogenesis of IBS include linoleic acid metabolism; GABAergic synapse; biosynthesis of unsaturated fatty acids; valine, leucine and isoleucine biosynthesis; ovarian steroidogenesis; and others. In addition, a total of 103 significant metabolites were selected to distinguish active IBS from inactive IBS patients. Tyrosine metabolism, dopaminergic synapse and neuroactive ligand-receptor interaction were found to be closely related to the disease activity of IBS. Furthermore, three potential metabolites including quinate, stearidonic acid (SDA) and capric acid (CA) could significantly differ IBS patients from NC group. On the other hand, 1-methyladenosine (m1A), genipin, methylmalonic acid (MMA) and ascorbate could significantly differentiated active IBS from inactive IBS patients. Conclusion In conclusion, this study demonstrated the characteristic plasma metabolic profiles between IBS group and NC group, as well as between active and inactive IBS patients by using an untargeted LC/MS metabolomics profiling approach. In this study, quinate, SDA and CA were identified as potential diagnostic biomarkers for IBS. Additionally, m1A, genipin, MMA and ascorbate could serve as potential biomarkers for evaluating IBS activity. These findings might provide potential valuable insights for developing therapeutic strategies to manage IBS in the future.